Nonlinear climatic controls and land-use modulations of net ecosystem productivity: Implications for regional carbon management - Xichen Mi; Qing Yu; Tianci Yao; He Sun (Journal of Cleaner Production, 2026)

Effects of Al and Ca on the reactivity of impurity Ti during gas-blowing refining of industrial silicon melt - Zuhan Shan; Fen Zou; Xichen Sun; Pengliang He; Jijun Wu; Kuixian Wei; Wenhui Ma (Chemical Engineering Journal, 2026)

Biomimetic polydopamine-intercalated MgAl-layered double hydroxide for effective skin photoprotection and photodamage recovery - Pengqi Zhu; Xichen Sun; Ye Cai; Mingchen Zhao; Ruiping Zhang; Jinghua Sun (Journal of Photochemistry and Photobiology B: Biology, 2026)

Dynamic boronic ester bonded shape memory elastomer with high mechanical strength and energy dissipation properties for vibration and impact protection - Qili Yu; Guangyu Sun; Xichen Yang; Qunfu Fan; Yujie Chen; Hezhou Liu (Chemical Engineering Journal, 2025)

Synergistic inactivation effect of ultrasound and nano-emulsified basil essential oil on the metabolic responses of Salmonella on sprouts - Zifei Liu; Peiwen Sun; Xichen He; Dingsong Lin; Lijing Ke; Chao Shi; Hongshun Yang; Lingchi Deng; Zejia Lin; Lin Chen (International Journal of Food Microbiology, 2025)

Inhibition of Neospora caninum activity by niclosamide: Evidence from in vitro and in vivo studies - Feixue Liu; Xin Li; Liuzhenxiu Yan; Xu Zhang; Jin Sun; Haitao Su; Lu Li; Sining Chen; Lanbi Gao; Pengtao Gong; Nan Zhang; Xichen Zhang; et al. (Veterinary Parasitology, 2025)

The instabilities of the Antarctic slope current in an idealized model - Chengyan Liu; Zhaomin Wang; Xi Liang; Xiang Li; Xianxian Han; Wenjin Sun; Yang Wu; Xichen Li; Chen Cheng (Journal of Marine Systems, 2025)

Exploring the potential of ultrasound combined with sucrose treatments for germination and growth of sunflower sprouts - Zifei Liu; Peiwen Sun; Xichen He; Dingsong Lin; Hongshun Yang; Zejia Lin; Lin Chen (Food Bioscience, 2024)

China’s Recent Progresses in Polar Climate Change and Its Interactions with the Global Climate System - Xichen Li; Xianyao Chen; Bingyi Wu; Xiao Cheng; Minghu Ding; Ruibo Lei; Di Qi; Qizhen Sun; Xiaoyu Wang; Wenli Zhong; Lei Zheng; Meijiao Xin; et al. (Advances in Atmospheric Sciences, 2023)

Deoxygenation-based CO2 mitigation: State-of-the-art, challenges, and prospects - Zhao Sun; Xichen Wang; Lunbo Duan; Zhiqiang Sun (Current Opinion in Green and Sustainable Chemistry, 2023)

Air-Backed Aluminum Shells Subjected to Underwater Penetration: Torpedo Interception Simulations - Chucai Peng; Chufan Ding; Bin Chen; Xichen Sun; Weibing Li; Taotao Qin; Jun Feng (Journal of Marine Science and Engineering, 2023)
Underwater torpedoes have become a serious threat to ocean liners and warships, and the interception against attacking torpedoes is always the hotspot in marine engineering. To simulate the underwater torpedo interception by a high velocity projectile, this work numerically deals with the process of projectile water entry and sequent penetration into underwater aluminum shells, whereby conical and ogival nose projectiles are comparatively studied. With the arbitrary Lagrange–Euler (ALE) algorithm adopted to describe fluid medium, the projectile water entry model is developed and validated against the test data. Similarly, the penetration model validation is made by modeling a tungsten ball perforation on an aluminum plate. Covered by water fluid, the air-backed aluminum shell is utilized to simulate an underwater torpedo subjected to projectile impact. The numerical predictions of underwater penetration reveal that ogival nose projectiles have a superior performance in underwater motion and perforation while conical nose counterparts deteriorate the shell targets more severely. For 20 cm, 40 cm and 60 cm underwater depth scenarios, a numerical prediction suggests that the energy consumed by water is proportional to the water depth, meanwhile aluminum shell perforation absorbs almost the identical projectile kinetic energy. Such findings may shed some light on the nose shape optimization design of high velocity projectile intercepting underwater torpedoes.

Durable antibacterial and temperature regulated core-spun yarns for textile health and comfort applications - Wei Fan; Yao Zhang; Yanli Sun; Shujuan Wang; Cong Zhang; Xichen Yu; Weiting Wang; Kai Dong (Chemical Engineering Journal, 2023)

The importance of inter‐basin atmospheric teleconnection in the SST footprint of Atlantic multidecadal oscillation over western Pacific - Cheng Sun; Yusen Liu; Jiaqing Xue; Fred Kucharski; Jianping Li; Xichen Li (Climate Dynamics, 2021)